2020
DOI: 10.1097/psy.0000000000000857
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Prediagnosis Audiovestibular Dysfunction Versus Distress, Illness-Related Cognitions, and Behaviors in Predicted Ongoing Dizziness Handicap

Abstract: Objective People with chronic vestibular diseases experience variable degrees of self-perceived disability. However, longitudinal data examining the predictive validity of relevant clinical variables alongside psychological variables are limited. The present study examined whether these factors predict self-reported dizziness handicap 3 months after assessment and diagnosis. Methods Patients were recruited from a waiting list of a tertiary neuro-otology clinic and compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Reductions in avoidance and resting in response to symptoms was also greater in INVEST. It was surprising that all-or-nothing behaviour did not show a larger treatment effect, since our previous prospective data found this to be a strong predictor and was a predominant feature of INVEST [ 17 , 18 ]. Both groups improved so this may also reflect similarities between the interventions in terms of pacing and graded exercise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reductions in avoidance and resting in response to symptoms was also greater in INVEST. It was surprising that all-or-nothing behaviour did not show a larger treatment effect, since our previous prospective data found this to be a strong predictor and was a predominant feature of INVEST [ 17 , 18 ]. Both groups improved so this may also reflect similarities between the interventions in terms of pacing and graded exercise.…”
Section: Discussionmentioning
confidence: 99%
“…To address this gap, we developed a combined CBT-VRT intervention based on existing research data and theoretical modelling of the psychological factors that contribute to dizziness handicap [ 17 , 18 ]. Based on those findings and working in partnership with patient representatives, we developed a patient manual.…”
Section: Introductionmentioning
confidence: 99%
“…For individuals experiencing persistent dizziness, a CBT protocol which remains contextually anchored to their experience of living with dizziness may ultimately promote better engagement with rehabilitation and improve health outcomes. We conducted a theoretical modelling prospective study which revealed the importance of a variety of illness-specific cognitive and behavioural factors in the experience of dizziness-related disability [ 17 , 18 ]. This was drawn together with a review of the literature to develop a model specific to dizziness (article in preparation), and we then used intervention mapping techniques [ 19 , 20 ] to design an intervention and detailed manual which integrated CBT methods into traditional VR.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of the baseline extent of dizziness-associated handicap on follow-up was also found in other studies. In therapy-naive patients with chronic vestibular diseases, the baseline handicap explained that most of the variance correlated with the handicap at a 3-month follow-up [ 23 ]. In patients with functional vertigo and dizziness subjected to a multimodal psychosomatic inpatient treatment, the vertigo-related handicap at admission was the only significant predictor of vertigo-related handicap at follow-up [ 14 ].…”
Section: Discussionmentioning
confidence: 99%